Operating Rules - McGill Community For Lifelong Learning (MCLL) (2022)

The Newsletter : Fall 2020: Volume 31, No. 2 - McGill Community For Lifelong Learning (MCLL) (2020)
Number of pages: 12

Fall 2022 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 12

Annual Report : 2020-2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Survey of MCLL Moderator Engagement : Report to the MCLL Council - McGill Community For Lifelong Learning (MCLL) (2021)
In December 2019, Council requested that the Planning Committee create and administer a survey of moderators to inquire about their engagement in the MCLL community in the service of retaining and recruiting moderators. Due to the COVID-19 outbreak and the high-priority burden the pandemic put on various committees, the survey was delayed until late in the Fall 2020 term. This document reports on the survey results and includes, in appendices, the survey questions as well as the detailed results including all comments received by respondents.

November 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 7

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 3

September 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 6